Peran Bank Wakaf Mikro Syariah dalam Pemberdayaan Ekonomi Masyarakat (Studi Empiris BWM Ponpes Mawaridussalam) - suglia, ella annissa (Jurnal Ilmiah Ekonomi Islam, 2024)
The problem of poverty and economic inequality has always been a major problem in the presence of social disparities in Indonesian society. The role of financial institutions in the distribution of funding and financing has an important role in empowering the economic activity of the community. This research aims to find out the role of Bank Wakaf Micro Shariah Pondok Pesantren Mawaridussalam in Economic Empowerment of the Society. This study uses qualitative research techniques with a descriptive approach. The types of data used in this study are primary data and secondary data. Data collection techniques are done with observations and interviews. The results of this study show that the role played by Bank Wakaf Micro Shariah Pondok Pesantren in empowering the economy of the community around the mansion is by providing financing and support through weekly activities (halmi). The result of the research is that Mawaridussalam is trained through the Wakaf Micro Bank. The Shariah has a role in empowering the community by providing business capital loans for micro-economy, getting rid of rent and interest bars, increasing daily income and adding religious science.